Efeitos da contaminação ambiental por mancozebe em girinos de Physalaemus henselii (PETERS, 1872) (Anura: Leptodactylidae): uma espécie termossensível e de distribuição restrita - Pereira, Guilherme de Azambuja (2020)
Native habitats experience dramatic conversion rates by expanding agriculture, resulting in environmental contamination and impacts on wildlife. Mancozeb (Mz) is a best-selling broad-spectrum fungicide in the world, which negatively affects non-target organisms. Negative effects on survival, growth rates, oxidative stress and genotoxicity have been reported in animals exposed to Mz. However, little is known about the effects of Mz on native aquatic fauna, since most studies are restricted to established animal models, such as invertebrates, fish, and rats. Here, we tested the effects of Mz on an amphibian species in the Neotropical region. We used tadpoles of Physalaemus henselii to determine the Lethal Concentration of Mancozeb (LC50) and the possible sublethal effects of this fungicide on tadpoles, using oxidative stress markers and redox alterations. In addition, we tested the effects of Mz on the critical thermal maximum (CTmax) and on the expression of heat shock proteins (HSP70). We recorded that acute exposure to the fungicide decreased the tadpole survival. Tadpoles exposed to a sublethal dose of 2mg/L Mz showed lower activity of catalase (CAT) and superoxide dismutase (SOD) enzymes, in addition to lower protein thiols (PSH) levels. Besides, there was an increase in glutathione S-transferase (GST) activity and greater lipid peroxidation. The exposure also negatively affected the thermal physiology and expression of the heat shock protein in the tadpoles of Physalaemus henselii, inducing an increase in the activity of HSP70 and reducing the thermal maximum supported by the tadpoles. There was an increase in HSP70 expression in tadpoles exposed to Mancozeb and in tadpoles subjected to heat treatment. The results obtained here demonstrated that the fungicide Mancozeb, even in non-lethal doses and lower than those used in cultivation areas, negatively affects the cellular functioning of tadpoles. These results are worrisome as we currently face the global warming challenge in a scenario of accelerate conversion of native grasslands to croplands that expose organisms to several types of agrochemicals.